PENGARUH MODEL RADEC (READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PADA SISWA KELAS IV SDN BIRINGKALORO KABUPATEN GOWA - Mutiara; Abdul Azis; Try Gustaf Said (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the RADEC model on the learning outcomes of fourth-grade students in Pancasila Education at SDN Biringkaloro, Gowa Regency, using a One Group Pretest–Posttest experimental design. The sample consisted of 25 students selected through total sampling, with data collected through tests, observations, and documentation, and analyzed using descriptive and inferential statistics (paired sample t-test assisted by SPSS). The results showed an increase in the average score from 65.00 to 88.00 and learning mastery from 40% to 100%, supported by a high level of implementation (86%) and a significance value of 0.001 (<0.05). Therefore, the RADEC model has a significant and positive effect on improving students’ learning outcomes and understanding of Pancasila Education material